Money Demand in the Netherlands - Traa, Bob. (Washington, D.C. : International Monetary Fund, 1991)
This paper analyzes the demand for narrow money balances in the Netherlands. Demand for narrow money balances had increased markedly in relation to GNP in the Netherlands throughout the 1980s. This phenomenon could not be explained satisfactorily with traditional Goldfeld-type money demand functions which had performed well until that time. Drawing on advances in dynamic modeling from the error corrections and cointegration literature, and incorporating yield-curve effects and the exchange rate of the guilder with the U.S. dollar as additional monetary indicators significantly improves the performance of money demand estimates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet